Knowledge in Inﬂammatory Bowel Disease: Translation to Portuguese, Validation, and Clinical Application of the IBD-KNOW Questionnaire - Sequeira,Cristiana (2024)
Abstract Background/Aims: Inﬂammatory bowel disease (IBD)-related knowledge empowers patients, providing the development of adaptative coping strategies. Recently, a more comprehensive questionnaire for evaluating IBD-related knowledge was developed, the IBD-KNOW. The main aim of our study was to translate to Portuguese and validate the IBD-KNOW questionnaire. We also explored the predictors of high scores of disease-related knowledge and the effect of knowledge on health-related quality of life (HRQoL) and therapeutic adherence. Methods: This is an observational, unicentric, and cross-sectional study. We translated and adapted the original English version of the IBD-KNOW questionnaire into Portuguese. Afterwards, IBD patients in the outpatient clinics were invited to ﬁll out a multimodal form including the Portuguese version of IBD-KNOW, a visual analogue scale (VAS) of self-perceived knowledge, the Portuguese version of Short IBD Questionnaire (SIBDQ) and the Portuguese version of Morisky Adherence Scale 8-item (MMAS-8). Demographic and disease characteristics were collected. We assessed validity (through discriminate validity among non-IBD volunteers and correlation between IBD-KNOW and VAS) and reliability (through internal consistency, test-retest, and intraclass correlation). Statistical analysis was performed using SPSS version 25.0. Results: The mean IBD-KNOW score was signiﬁcantly different among non-IBD validation group (doctors: 23, nurses: 18, and non-medical volunteers: 12, p < 0.001). IBD-KNOW showed a high internal consistency (Cronbach’s α 0.78) and intraclass correlation (0.90). As expected, the IBD-KNOW score was positively correlated with VAS for self-perceived knowledge (r =0.45, p < 0.001). One hundred and one patients with IBD (54 with ulcerative colitis and 47 with Crohn’s disease) completed the questionnaire at baseline. Multivariate analyses showed that a high IBD-KNOW score was associated with longer disease duration (OR: 2.59 [CI 1.11-5.74]; p = 0.04), previous hospitalization (OR: 3.63 [CI 1.301-9.96]; p = 0.01), current biologic treatment (OR: 3.37 [CI 1.31-8.65]; p = 0.02), and higher educational level (OR: 4.66 [CI 1.74-10.21]; p = 0.02). Moreover, there was no signiﬁcant correlation between overall IBD-KNOW and SIBDQ, nor between IBD treatment adherence (MMAS-8 = 8) and a higher mean IBD-KNOW score (p = 0.552). Conclusion: The Portuguese version of IBD-KNOW is a simple, valid, and reliable tool for assessing IBD-related knowledge. Longer disease duration, hospitalization, use of biologics, and higher educational level are associated with higher levels of knowledge. Higher patient knowledge was not associated with higher HRQoL and adherence to therapy.